Pendampingan Sertifikasi Halal Produk Usaha Mikro dan Kecil Bagi Masyarakat Desa Bajeman Kecamatan Tragah Kabupaten Bangkalan - Taufiqur Rahman; Farid Ardyansyah; Kurnia Fitri Salsabila; Rosita Ramadhani (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2025)
The obligation to implement halal certification for micro and small business products will end in October 2026. Therefore, the sustainability of micro and small business actors must be taken more seriously and need to be protected from unfair competition, specifically in Bajeman Tragah village, Bangkalan Regency because many business actors in Bajeman Village do not fully understand the obligation of halal certification of products and do not understand the procedures for registering halal certification. The focus of this activity is to provide training and mentoring to business actors so that the business products get legal certainty and halal legality from BPJPH with the mechanisms established by the Indonesian government. The products must be halal and in accordance with Islamic law, where cleanliness, quality, and safety of the production process must be based on a halal quality management system. The mentoring technique implemented is to help business actors to be able to understand and be aware of the obligation of halal certification of their products, then accompany them in the halal certification registration process starting with obtaining NIB, the Self-Declare SJPH Process and until obtaining Halal Product certification. The halal certification mentoring program for micro and small businesses in Bajeman Village, Bangkalan will be conducted over a four-month period, from August 2025 to November 2025. The program aims to facilitate the process of obtaining halal product certification for businesses in Bajeman Village, Bangkalan. The program will raise awareness among the micro and small business actors to register their products to obtain halal product certification from The Government of Indonesia.